Steroid-responsive recurrent limbic encephalitis associated with small cell lung cancer and neuropil antibodies. - Tüzün, E; Yaka, E; Zuliani, L; Içöz, S; Baklan, B; Birişik, O; Kurd, P; Akman-Demir, G; Vincent, A; Akdal, G (Springer-Verlag Italia s.r.l., 2011)
Paraneoplastic limbic encephalitis (PLE) associated with small cell lung cancer (SCLC) often presents with antibodies to intracellular antigens and a poor outcome even after tumor resection and immunotherapy. We report a PLE patient presenting with generalized seizures, shortterm memory impairment and medial temporal lobe hyperintensity in MRI. Initial screening revealed significantly elevated thyroid antibody levels suggesting Hashimoto's encephalopathy. Following methylprednisolone treatment, her seizures ceased, MRI findings disappeared and memory impairment showed a partial resolution in 5 months. Two months later, she developed further generalized seizures. Chest X-ray showed a mass lesion, which was demonstrated by needle biopsy to be a small cell lung carcinoma (SCLC). The panel of onconeural antibodies including cell-membrane antigens was negative. However, the patient's serum and cerebrospinal fluid IgG, obtained during both exacerbations, immunolabeled cytoplasm and dendrites of Purkinje cells, cerebellar and hippocampal molecular layers, basal ganglia, thalamus, and the surface of cultured hippocampal neurons, in a manner distinct from previously identified neuropil antibodies associated with SCLC. These neuropil antibodies appear to be associated with a favorable response to treatment. Further studies are required for determination of the target antigen.